Cr3+ substituted spinel ferrite nanoparticles with high coercivity. (9th May 2016) - Zhang, Wei; Zuo, Xudong; Zhang, Dongmei; Wu, Chengwei; Silva, S Ravi P
Abstract: The low coercivity of spinel ferrites is a major barrier that significantly limits their use in high density magnetic recording applications. By controlling the substituting content of Cr 3+, in this article we describe how magnetic CoCr x Fe2− x O4 (0 < x < 1.2) nanoparticles with coercivity of up to 6.4 kOe were successfully obtained by the hydrothermal process. The high coercivity is attributed to the synergetic effects of magnetocrystalline anisotropy and the nanoscale size effect. X-ray diffraction analysis confirmed the spinel structure of the nanoparticles with transmission electron microscopy (TEM) suggesting regular tetragonal morphology. The TEM indicated an edge length ranging from 15 nm to 150 nm, which increases monotonically with increasing Cr content. Raman analyses supported the proposed model on the formation mechanism of the nanoparticles, i.e. heterogeneous and homogeneous nucleation.